The use of Eichhornia crassipes in a surface flow wetland system for removing nitrogen and phosphorus of pig wastewater after anaerobic treatment (biogas) process - Nguyet, Vu Thi; Tua, Tran Van; Kien, Nguyen Trung; Kim, Dang Dinh (Academia Journal of Biology, 2015)
This paper presents the  preliminary results on the removing capasity of nitrogen and phosphorus in pig wastewater after anaerobic (biogas) process at pilot scale by using Eichhornia crassipes. The experimental results showed that the wastewater loading rate 50 l/m2.day with initial concentrations of 89.79 mgTN/l and 15.69 mgTP/l gave removal efficiency of 65.79% và 55.19%, respectively, while the wastewater loading rate 100 l/m2.day has removal efficiency of 39.70 % for TN and 43.29% for TP in case of input concentrations 100.38 mgTN/l and 12.52 TP/l. Thus, at the loading rate 50 l/m2.day, the removed quantity of TN and TP was of 2,953.64 mgTN/m2.day và 432.96 mgTP/m2.day, while at the loading rate 100 l/m2.day, this value was 3985.09 mgTN/m2.day và 541.99 mgTP/m2.day. The obtained results indicated that the surface flow wetland system, using Eichhornia crassipes has a rather high TN and TP removal efficiency at simple operation so that it could be feasible if applied for treating pig wastewater. However, the system should be functioned longer for taking data and for evaluating it’s stability.